Precursor frequency analysis of cytotoxic T lymphocytes to pre-erythrocytic antigens of Plasmodium falciparum in West Africa. - Plebanski, M; Aidoo, M; Whittle, H; Hill, A (1997)
Some individuals living in malaria-endemic areas have CTL to Plasmodium falciparum liver stage Ags. We have quantified these CTL responses using limiting dilution analysis studies on the peripheral blood cells of naturally exposed Gambian donors. CTL precursor frequencies were determined to a wide range of epitopes derived from different liver stage Ags (liver stage protein 1, circumsporozoite protein, thrombospondin-related anonymous protein, and sporozoite threonine/asparagine-rich protein) restricted through common HLA alleles present in this population (HLA-A2.1, -A2.2, -B7, -B8, -B35, and B53). Precursor frequencies were between 17 and 98/million PBMC and correlated with the levels of specific lysis in parallel bulk cultures. The quantitative nature of limiting dilution assay analysis revealed varying degrees of immunodominance in the CTL responses to different epitopes within single proteins (thrombospondin related anonymous protein: tr42, tr43, tr26, tr29, and tr39; circumsporozoite protein: cp6, cp26, and cp29) and within individual donors. The temporal stability of some of these CTL responses was determined over a 4-yr period. This is the first quantitative study of CTL specific for any plasmodial species or nonviral pathogen in humans and provides a basis for a multiepitope approach to malaria vaccination.